2017
DOI: 10.1016/j.jpurol.2017.03.034
|View full text |Cite
|
Sign up to set email alerts
|

Indicators and outcomes of transfer to tertiary pediatric hospitals for patients with testicular torsion

Abstract: Patients are more likely to be transferred to our tertiary pediatric facility for management of testicular torsion during the night or weekend. Transferring patients for management of testicular torsion delays definitive management and threatens testicular viability, especially in those transferred greater distances. Urologists at the facility of initial patient presentation should correct testicular torsion when able.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 17 publications
1
23
0
Order By: Relevance
“…These findings agree with Bayne’s ( 26 ), that reported a positive association between inter-hospital transfer and orchidectomy, especially in boys with presentation delay <24 hours. Likewise, Preece and associates ( 14 ) found that patients transferred within 24 hours of symptoms to their tertiary hospital had twice the probability of testicular loss (30%, versus 15% for those first seen at their tertiary hospital). Although investigators from California ( 15 ) described comparable salvage rates between patients transferred or examined at their tertiary hospital, the mean time from symptoms to operating room between them differed by only 83 minutes.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…These findings agree with Bayne’s ( 26 ), that reported a positive association between inter-hospital transfer and orchidectomy, especially in boys with presentation delay <24 hours. Likewise, Preece and associates ( 14 ) found that patients transferred within 24 hours of symptoms to their tertiary hospital had twice the probability of testicular loss (30%, versus 15% for those first seen at their tertiary hospital). Although investigators from California ( 15 ) described comparable salvage rates between patients transferred or examined at their tertiary hospital, the mean time from symptoms to operating room between them differed by only 83 minutes.…”
Section: Discussionmentioning
confidence: 96%
“…While the time interval between symptoms and first medical assessment, i.e. presentation delay, rests upon the patient’s awareness of the disease and medical care availability ( 11 - 13 ), delays from this first assessment until evaluation at the treating institution have been associated with the first examining physician’s clinical diagnosis and subsequent action, such as imaging studies orders and inter-hospital patient referral and transfer ( 14 - 16 ). This information, however, comes from economically advanced countries, and although one may postulate that similar associations should also be observed in emerging countries, region-specific data is necessary to ascertain not only the existence but also the magnitude of these associations.…”
Section: Introductionmentioning
confidence: 99%
“…Zini et al [13] showed that the delay between the patients' arrival at the emergency department and the surgery was 2.6 times longer when an ultrasound was performed (p < 0.001). Preece et al [14] made the same finding even though the correlation was not significant. Therefore, we agree with Sauvat et al [15] and Zini et al [13] that, if there is a slightest doubt, surgical exploration should immediately be carried out in order to reduce the management delay and hence the risk of orchiectomy.…”
Section: Discussionmentioning
confidence: 76%
“…Previous studies have reported associations between transfer of patients to tertiary units and increased risk of orchidectomy, 17,18 and adherence to the RCS recommendations should reduce the delay in definitive management. Reducing the number of urgent transfers for suspected testicular torsion also minimises the burden on emergency ambulance services in having to undertake these journeys (which entail additional risks to patient, ambulance crew and general public) along with the non-availability of the ambulance for other emergencies at a time of increasing demand.…”
Section: Discussionmentioning
confidence: 99%